In vitro study the effect of flavonoid routine in cassava leaves (manihot esculenta c.) on the replication of dengue virus serotype 1 strain new guinea C - Dery Handaiana Putra Galuh Pangestu; Dadan Ramadhan Apriyanto; Sri Marfuati; Beti Ernawati Dewi (Science Midwifery, 2026)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus with clinical manifestations of fever, muscle pain and joint pain accompanied by leukopenia, rash, lymphadenopathy and thrombocytopenia. According to WHO, DHF is still a major health problem in Indonesia, while dengue antiviral therapy does not yet exist, but several studies have found the potential of cassava leaves because they contain routine flavonoid compounds that function as antivirals. Objective: To determine the effect of routine flavonoids from cassava leaves (Manihot esculenta C.) on the replication of Dengue virus serotype 1 strain New Guinea C in Vitro by analyzing the 50% inhibitory concentration (IC50), 50% cytotoxic concentration (CC50), and selectivity index. Method: The research was experimental with a post-test control group design. This study used 7 groups, namely 1 control group and 6 treatment groups. The treatment group consisted of routine administration of Flavonoids from cassava leaves (Manihot esculenta C.) with concentrations of 50 µg/ml, 25 µg/ml, 12.5 µg/ml, 6.25 µg/ml, 3.125 µg/ml and 1.5 µg/ml. The control group (K) was given 0.2% Dimethyl sulfoxide (DMSO). Data were tested using the Kruskal Wallis test. Results: In the Kruskal Wallis test, there was an effect of routine Flavonoids on dengue virus replication (p value = 0.006). The IC50 value obtained at a concentration of 3.36 µg/ml was declared very strong inhibition, and the CC50 at a concentration of 17.48 µg/ml was declared toxic, for the Selectivity Index obtained a value of 5.2 declared safe in its use. Conclusion: Routine flavonoids in cassava leaves (Manihot esculenta C.) have an effect on the replication of Dengue virus Serotype 1 Strain New Guinea C in Vitro.